GOING DIGITAL, EARNING MORE: THE IMPACT OF DIGITIZATION ON MSMEs REVENUE - Kartomo, Kartomo; Sapriyadi, Sapriyadi (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
Micro, Small, And Medium Enterprises (MSMEs) have proven to be economic contributors that create many new jobs and increase household incomes. Although various efforts have been made to develop MSMEs, many MSMEs still have difficulty accessing business financing, lack managerial skills, have marketing constraints, and have poor administrative and financial systems, thus limiting their ability to develop their businesses and increase income. This study aims to determine the influence of digitalization on the income of MSMEs actors. This study uses a quantitative approach using ordinal logistic regression method. The results show that the variables of service digitization, administrative digitalization, and product distribution digitalization do not significantly affect MSMEs income. Meanwhile, the variables of financial digitalization and marketing digitalization have a significant effect on MSMEs income. The results of the opportunity estimation show that MSMEs actors who use financial digitalization and marketing digitalization in their businesses have high-income opportunities as well as lower and less stagnant income opportunities compared to MSMEs actors who have not used financial digitalization and marketing digitalization in their companies. Policy recommendations include expanding access to digital financial tools, providing marketing training, and improving internet infrastructure to support MSMEs income growth through digitalization.